(untitled) (Bangladesh Journal of Zoology, 2021)
This study deals with the length-weight relationship and relative condition factor (Kn) of 2480 specimens of Rhinomugil corsula (Hamilton, 1822), ranging from 3.5 cm to 29.5 cm total length and 0.40 g to 235.34 g weight, sampled monthly for two years period from March 2016 to February 2018 from the Sitakunda Coast of the Bay of Bengal, Bangladesh. Arithmetic form of equations for length (TL) and weight (W) of fish showed curvilinear relationships in male: W=0.0081TL3.016, female: W= 0.0083TL3.058 and combined sex: W=0.0076TL3.052, while logarithmic scale showed linear relationships in male: LogW=-2.122+3.016LogTL, female: LogW=-2.09+3.058 TL and combined sex: LogW=-2.121+3.052TL. In all the cases the coefficient of correlations between length and weight were positive and highly significant (P<0.01). The regression coefficient ‘b’ values were found to be 3.01±0.11, 3.06±0.12 and 3.05±0.12 for male, female and combined sexes, respectively for two years period together. When ‘t’ test was done, the growth was found to be isometric in case of male and combined sex and positive allometric in case of female. The relative condition factor (Kn) varied from 1.0003-1.009, 1.001-1.008 and 1.001-1.008, respectively, for male, female and combined sex in 2016-17, whereas 1.001-1.007, 1.003-1.006 and 0.992-1.008 respectively in 2017-18. The Kn values were always around ‘1’ or a little bit more than ‘1’ for length groups as well as monthly, indicating the excellent growth and robustness of fish due to favorable environmental condition prevailing in the habitat of the fish, in the Sitakunda coast of the Bay of Bengal. Bangladesh J. Zool. 49(1): 91-103, 2021